'Become what you are': subcultural identity and 'insider teaching' in youth studies. Issue 1 (2nd January 2022) - Green, Ben; Feldman-Barrett, Christine
ABSTRACT: This article responds to a trend of people pursuing academic careers after, or alongside, participation in popular music scenes and subcultures, applying scholarly perspectives on how identity can inform teaching and recognising the pedagogical benefits of teachers drawing on their multifaceted lives. The authors reflect critically on their pedagogical approach in teaching a youth studies sociology course and consider how their respective musical and subcultural backgrounds inform their professional lives as educators. Importantly, the article highlights the ways in which the authors' 'youth culture biographies' can become useful resources for exploring youth studies concepts with students. It is argued that identity-based teaching practices including 'insider teaching' can not only help to illustrate course ideas and make them more relatable for students, but more broadly empower students to practice reflexivity toward their own experiences, contrary to the depersonalising tendencies of neoliberal education.